Proposta de uma Abordagem de Sincronização Multimaster Utilizando Dispositivos Móveis - (:unkn) unknown (Universidade Federal do Pampa, 2013)
The wireless and mobile technologies use by the current society is a reality. The ability to control the characteristics associated with mobility offer great opportunities for the smarter solutions development. Currently in software application engineering, most research effort is devoted to models, concepts and tools to understand mobile data and become viable in a distributed application. This work aims the software tool creation for mobile devices that allows access to real-time data from the system, keeping it consistent, aiming high availability through synchronization techniques for the multimaster database, using the tool SQLyog Job Agent (SJA). In addition, also development a control application for participants accreditation in academic events. As a result, were performed interact tests with the database, analyzing the proposed environment synchronization and observing the data persistence and high availability.
Keywords: Sincronização; Banco de dados; Dispositivos móveis; CNPQ::ENGENHARIAS